Index Card Match to Increase Student Activity in Elementary School - Isna Rahmawati (Jurnal Pendidikan Modern, 2017)
This study aimed to improve students' activeness by using Index Card Match for grade5 in Social Studies lesson of SDN 4 Barenglor. The active learning strategy of IndexCard Match type is a strategy of repetition (review) of the material, so the students canrecall the material they have learned. This research was a classroom action researchwith a cycle model from Kemmis & Taggart. This research taken two cycles, that wascycle I and cycle II. The data obtained are presented in the table, and analyzed withdescriptive qualitative method. The results showed that the application of Index CardMatch in in Social Studies learning can improve students' activity for Grade 5 of SDN4 Barenglor. Student activeness were increasing from cycle to cycle. Percentage ofstudents' activity before the action is only 18.75% and it increased into 45.87% incycle 1. In cycle 2 there was an increase of 76.39% of students participate actively inlearning activities. In addition to student activeness, student learning outcomes werealso increased. In the first cycle Social Studies learning with Index Card Match hadthe average value of student learning outcomes of pre-cycle amounted to 73.23% withthe percentage of learning completeness only amounted to 47.94%. It increased to78.17 with student completeness reaching 62.52%. In cycle 2, the average value ofstudent learning increased into 81.63 and students' learning completeness reaches91.69%.